Política de informação: o Programa Cultura Viva do Ministério da Cultura - Maria Cristina Brasil Magnani (2011)
Information Science was consolidated after the Second World War, from interest of countries in the process of information transfer, necessary to achieve scientific and technological development. In the 1990s, the Information Science developed more or less autonomous policies and practices that gained prominence with the deployment of information and communication infrastructures. Given the advances and convergence of digital technologies and global information flows, it is seen the need for an approach to the studies of Information Science, incorporating materials from different disciplines and information practices and sharing. The purpose of this research was to use the concept of information regime as a way of framing, in the culture area, these subjects and disciplines, bringing together actors, technologies, networks and information systems and practices within a framework allowing to analyze the different strategies of creation, use and sharing of information and to reveal different political positions within this framework. The analysis has focused on the Digital Culture Action developed under the Living Culture Program which has being developed by the Ministry of Culture, since 2004. The research has looked at the constitutional documents of the program, elements that should identify the characteristics of an information regime and information policies underlying this frame, within the Action under review. As a result, it wasfound that the approach of information regime offers a valuable way for Information Science studies, which goes beyond the disciplinary perspective, which historically led this field and that reveals in different views, political positions, which permeate social information practices today.